2021
DOI: 10.3390/biology10030239
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about Testicular Self-Examination among Polish Males

Abstract: Introduction: Epidemiological data indicate an increased incidence of testicular cancer (TC), making it the most common malignant tumor in men from aged 15–45. Oncological and urological associations recommend that men with specific TC risk factors should regularly perform a testicular self-exam (TSE). The aim of the study was to discover the attitudes among Polish males regarding TSE and factors (environmental, social, educational) that affect intention to perform TSE. Methods: An original survey containing 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 28 publications
(38 reference statements)
2
14
0
Order By: Relevance
“…Other Polish scientists have also reached similar conclusions [ 25 ].The authors show that 57.5% of Polish men do not perform TSE at all. Among the group of people who perform the test: 12% do it once a month, 5% once a quarter, and 26% once every six months.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Other Polish scientists have also reached similar conclusions [ 25 ].The authors show that 57.5% of Polish men do not perform TSE at all. Among the group of people who perform the test: 12% do it once a month, 5% once a quarter, and 26% once every six months.…”
Section: Discussionsupporting
confidence: 70%
“…Other, less frequently indicated factors were: family history of TC, recommendation of a general practitioner (GP) and social campaigns. The paper [ 25 ] emphasizes the importance of discussion with GP about TC, therefore teaching TSE by a doctor increases the chances that the patient will perform it. A patient instructed by a doctor has more confidence that he/she performs the tests correctly.…”
Section: Discussionmentioning
confidence: 99%
“…One potential solution is the development of trusted Internet resources for patients affiliated with renowned clinics or scientific bodies. Another option is the creation of social campaigns and awareness programs oriented at promoting testicular self-examination [ 14 , 15 , 16 , 17 , 18 , 19 ] and early detection of testicular malignancies [ 35 , 36 , 37 , 38 ]. Examples of such initiatives are Testicular Cancer Awareness Month and Men’s Health Awareness Month, held every April and November, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies demonstrated that the knowledge of the early symptoms of testicular cancer among males at risk is suboptimal [ 9 , 10 , 11 , 12 , 13 ], with the practice of testicular self-examination, a basic screening test, not being as common as recommended [ 14 , 15 , 16 , 17 , 18 , 19 ]. However, still little is known about the causes of diagnostic delay in men with testicular malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…5 TSE is a simple screening method that can assist identify abnormal changes in testis tissue and appearance. 4,6 For men over the age of 15, TSE is advised to be performed once per month. 6 There is evidence to suggest that men worldwide tend to have some basic knowledge of testicular cancer, but not about TSE.…”
Section: Background For the Studymentioning
confidence: 99%